Consensus control for distributed power tracking by device-level digital twin agents - Wang, Yanan; Guo, Zhimin; Pang, Yuhang; Gao, Kaiqiang; Zhao, Jian (Frontiers in Energy Research, 2023)
With the development of electronic and software, it is possible for the digital twin agents can be seen as digital counterparts for the process of optimization, control, and monitoring process for the real power grid. While more and more regulation resources are connected to the power grid, it is hard for independent system operators to employ a centralized controller to reach power tracking and balance. Therefore, a device-level-based digital twin is employed to monitor the signal from physic to computer-aid design for power tracking. Besides, the consensus control-based distributed power tracking is proposed to execute physical-model simulation for the power grid. Meanwhile, the communication network is designed for realistic signal exchange. The combination of the proposed distributed power tracking method and communication network can accelerate computational efficiency and protect the privacy of the regulation resources. Finally, the performance of the proposed distributed power tracking method is validated in a simulation system with 10 regulation resources.